2018
DOI: 10.1007/s10182-018-0328-5
|View full text |Cite
|
Sign up to set email alerts
|

Change-in-mean tests in long-memory time series: a review of recent developments

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Applying their test, we rejected the null hypothesis of a constant mean with a d~1. We note, however, that simulation studies have shown that this test can be unreliable, even for mid-range values of d. In fact, Wenger et al [107] have shown that even for fractionally integrated white noise vectors, this test is biased toward rejection. As a workaround, we first checked via a Whittle estimator to have a clearer picture of the order of fractional integration.…”
Section: Structural Breaks Via Meanmentioning
confidence: 68%
“…Applying their test, we rejected the null hypothesis of a constant mean with a d~1. We note, however, that simulation studies have shown that this test can be unreliable, even for mid-range values of d. In fact, Wenger et al [107] have shown that even for fractionally integrated white noise vectors, this test is biased toward rejection. As a workaround, we first checked via a Whittle estimator to have a clearer picture of the order of fractional integration.…”
Section: Structural Breaks Via Meanmentioning
confidence: 68%
“…The testing problem is addressed by several papers such as Wang (2008), Shao (2011), Dehling, Rooch, and Taqqu (2013), Iacone, Leybourne, and Taylor (2014), Betken (2016), and others, who employ a variety of competing testing principles. These are reviewed in Wenger, Leschinski, and Sibbertsen (2018). It is found that self-normalized tests are robust against size distortions in finite samples and the CUSUM testing principle tends to be the most powerful.…”
Section: Introductionmentioning
confidence: 99%
“…Complexity of segmentation may be different, from quite simple statistic based decision making, especially if differences in the data for different subprocesses are clear to notice (as a change of mean or variance) to very advanced techniques for a more complicated process. Interesting approaches used for the problem related to the changing of the location parameter (like mean) can be found in [33][34][35][36][37][38][39][40] while the methods for changing the scale parameter (like variance) are presented, for instance, in [33,[41][42][43][44][45][46][47][48]. A specific case is related to heavy-tailed processes [28][29][30][31] where we expect the impulsive behavior of the corresponding data.…”
Section: Introductionmentioning
confidence: 99%